Examining alterations in subjective sleep ratings in individuals with major depressive disorder receiving daily theta burst stimulation - Jennifer Cuda; David Smith; Arthur R. Chaves; Karina L. Fonseca; Jessica Drodge; Stacey Shim; Youssef Nasr; Maya El-Outa; Ram Brender; Ruxandra Antochi; Lisa McMurray; Rebecca Robillard; et al. (Journal of Affective Disorders Reports)
Background: Major depressive disorder is often accompanied by sleep disturbances, which have been found to influence response to antidepressant treatments. Repetitive transcranial magnetic stimulation (rTMS), including novel optimized protocols like theta burst stimulation (TBS), is an effective intervention for treatment-resistant depression, although little is known about the relationship between sleep and the antidepressant effects of this treatment. Methods: Sixty-six individuals with treatment-resistant depression received 4 to 6 weeks of daily TBS treatments targeting the left-unilateral or bilateral dorsolateral prefrontal cortex (DLPFC). Depression severity was measured using the Hamilton Rating Scale for Depression (HRSD-17) and subjective sleep using the Leeds Sleep Evaluation Questionnaire (LSEQ). Data was analyzed with linear mixed models and Spearman correlations. Results: TBS significantly reduced HRSD-17 scores and improved LSEQ subscales reflecting sleep quality, ease of awakening from sleep, and behavior following wakefulness. Improvements in symptoms of depression were associated with improvement in behavior following waking after 20 and 30 TBS sessions, but not with sleep quality. Limitations: Limitations include a limited sample size, lack of sham condition, subjective measures of sleep and variable number of treatments (20 or 30 TBS sessions). Conclusions: These findings suggest that TBS treatments concurrently improve subjective sleep quality and depression symptoms. Additionally, changes in depression more closely aligned with changes in sleep-related daytime functioning than with sleep quality per se. Further work is required to delineate how sleep improvements following neuromodulation may contribute to the antidepressant response.